Pengaruh Model Pembelajaran StudentTeamsAchievementDivisions (STAD) terhadap Keaktifan dan Hasil Belajar Kimia Materi Redoks melalui Siswa Kelas X TKJ SMK Negeri 2 Baubau Tahun Pelajaran 2018/2019 - Neneng Surasmin (Jurnal Akademik FKIP Unidayan, 2020)
The aim of this research is to describe the influence of Student Teams Achievement Division (STAD) learning model implementation to the activity and Chemistry learning result of students on redox subject matter in the grade X TKJ at SMK Negeri 2 Baubau in academic year 2018/2019. This research ordered to the type of quasi experiment research. Research instrument are observation sheet to know student’s activity and test that are pretest and post test to get student learning result data. Data analysis technique that used in this research is one way anova test. Research result shows that there is an influence of Student Teams Achievement Divisions (STAD) learning model implementation to the activity and Chemistry learning result of students on redox subject matter in the grade X TKJ at SMK Negeri 2 Baubau.